(untitled) (Research, Society and Development, 2022)
Teaching and learning process has been seen through new conceptions the last decades and with them new pedagogical strategies become more present in teachers’ curriculum. In this way, active methodologies are pedagogical tools that contribute to a dynamic teaching, since the use of such method strategies combined to Digital Information and Communication Technologies (DTIC) corroborate an education of an autonomous and protagonist student in the learning process. In this perspective, this study aims at making reflections about the use of active methodologies and DTIC in skill-based teaching of students, emphasizing teacher role in the process. For this, a bibliographic research survey was carried out using quantitative data analysis. Therefore, the basic authors are Zabala e Arnau, Perrenoud, Carvalho, Freire, Marcuschi, among others, they were used to support the teaching of competences from the use of active methodologies allied to DTIC. Checked the benefits of a teaching practice through active technologies, and also the role of the teacher in the effectiveness of the process provides skill-based teaching. Considering this, it was possible to undertand that teacher planning from active methodologies and the use of DTIC colaborate for the development of significative skills for an education of active, critical, protagonist, and researcher students in the process of learning how to know and how to do in the classroom and social environment.